Optimization of the growth conditions through response surface methodology and metabolomics for maximizing the auxin production by Pantoea agglomerans C1 - Melini, Francesca; Luziatelli, Francesca; Bonini, Paolo; Ficca, Anna Grazia; Melini, Valentina; Ruzzi, Maurizio (Frontiers in Microbiology, 2023)
The fermentative production of auxin/indole 3-acetate (IAA) using selected Pantoea agglomerans strains can be a promising approach to developing novel plant biostimulants for agriculture use. By integrating metabolomics and fermentation technologies, this study aimed to define the optimal culture conditions to obtain auxin/IAA-enriched plant postbiotics using P. agglomerans strain C1. Metabolomics analysis allowed us to demonstrate that the production of a selected array of compounds with plant growth-promoting- (IAA and hypoxanthine) and biocontrol activity (NS-5, cyclohexanone, homo-L-arginine, methyl hexadecenoic acid, and indole-3-carbinol) can be stimulated by cultivating this strain on minimal saline medium amended with sucrose as a carbon source. We applied a three-level-two-factor central composite design (CCD) based response surface methodology (RSM) to explore the impact of the independent variables (rotation speed and medium liquid-to-flask volume ratio) on the production of IAA and IAA precursors. The ANOVA component of the CCD indicated that all the process-independent variables investigated significantly impacted the auxin/IAA production by P. agglomerans strain C1. The optimum values of variables were a rotation speed of 180 rpm and a medium liquid-to-flask volume ratio of 1:10. Using the CCD-RSM method, we obtained a maximum indole auxin production of 208.30.4 mg IAAequ/L, which was a 40% increase compared to the growth conditions used in previous studies. Targeted metabolomics allowed us to demonstrate that the IAA product selectivity and the accumulation of the IAA precursor indole-3-pyruvic acid were significantly affected by the increase in the rotation speed and the aeration efficiency.